WORPLACE SAFETY IMPROVEMENT IN SME MANUFACTURING: A GOVERNMENT INTERVENTION - Zulkifly, Syazwan Syah; Zain, Izani Mohd; Hasan, Nor Halim; Baharudin, Mohd Rafee (MATTER: International Journal of Science and Technology, 2018)
Workplace accident in Malaysia shows an increasing trend in recent years with the SMEs sector is found to contribute 80-90% of the total number of accidents. Poor levels of occupational safety and health compliances within the SME manufacturings is determined to be the main cause of accidents. The underlying factors towards the compliance failures are financial constraint, lack of knowledge and expertise, limited human resources and inexistence of knowledgeable safety personnel. Therefore, the Department of Occupational Safety and Health Malaysia conducted an intervention programme with the objective is to improve the compliance of OSH within SME manufacturings. A total number of 59 SME manufacturings within Negeri Sembilan were selected based on their poor grading in OSH Compliance audits and a specific design intervention in the form of trainings then was conducted.The results of OSH compliance post-audit showed an improvement of 38% as compared to the pre-audit. The T-test analysis result also indicated a significant difference in OSH compliance grading among the participating SME manufacturing companies (P-value <0.01). In conclusion, government intervention conducted by DOSH could elevate OSHcompliance performance among the SME manufacturings.